Slagmarkens moral og risikofri krig med droner - Henriksen, Anders; Ringsmose, Jens (Politik, 2017)
The article examines the instinctive uneasiness many feel about the use of armed drones. Why is it, we ask, that so many people – including members of the armed forces – acknowledge that armed drones offer an expedient and legally defensible solution to pressing security challenges and yet feel uncomfortable about them? The main argument of the article is that much of the criticism of drone warfare is associated with an underlying ethically conditioned discomfort with so-called ‘riskless warfare.’ The very feature that makes drones so attractive to policy-makers and military commanders – their risk free deployment – is, paradoxically, also one of the primary causes why many feel fundamentally uncomfortable with them. To make this argument, we build on the works of Martin van Creveld and Paul W. Kahn.